2014
DOI: 10.1310/hpj4904-355
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous Drug Residue on Exterior Vial Surfaces: Evaluation of a Commercial Manufacturing Process

Abstract: Using validated extraction and analytic methods, all but 2 of the 230 tested vials were found to be free of surface drug contamination. Pharmacy leaders need to take an active role in promoting the need for clean HD vials. Manufacturers should be required to provide their clients with data derived from externally validated analytic studies, reporting the level of HD contamination on the exterior of their vial products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…A total of 24 studies from 11 countries were included (Germany (n=3 studies), Australia (n=1), Belgium (n=3), Canada (n=6), the USA (n=2), France (n=2), Japan (n=3), the Netherlands (n=2), the UK (n=1), Sweden (n=2), Switzerland (n=1)) (online supplementary appendix 1). 4 5 10–31 Sampling was done by wiping the containers (n=20) or by immersion (n=3). Liquid chromatography tandem-mass spectrometry (n=15) and gas chromatography tandem-mass spectrometry (n=15) were mostly used to quantify the drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 studies from 11 countries were included (Germany (n=3 studies), Australia (n=1), Belgium (n=3), Canada (n=6), the USA (n=2), France (n=2), Japan (n=3), the Netherlands (n=2), the UK (n=1), Sweden (n=2), Switzerland (n=1)) (online supplementary appendix 1). 4 5 10–31 Sampling was done by wiping the containers (n=20) or by immersion (n=3). Liquid chromatography tandem-mass spectrometry (n=15) and gas chromatography tandem-mass spectrometry (n=15) were mostly used to quantify the drugs.…”
Section: Resultsmentioning
confidence: 99%
“…We advocate for a thorough cleaning of the containers before they exit the production and are sent to the sites. Commercial protective overwrap can theoretically reduce this risk, but the protective wrapping itself was found to be contaminated 15 25 27. Protective wrapping added during the manufacturing process may contribute to a false sense of safety and they should be handled with the same precautions as other antineoplastic drug containers.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have shown that the outside of vials can be contaminated with hazardous drugs [Nyman et. al 2007;Power et al 2014]. This contamination could be from staff handling the vial, manufacturer, or distributer.…”
Section: Discussionmentioning
confidence: 99%
“…Należy pamiętać, że podczas przygotowania preparatów leków przeciwnowotworowych przez farmaceutów odpadami niebezpiecznymi są nie tylko puste lub napoczęte opakowania po lekach cytotoksycznych, lecz także wszystkie przed-mioty, które mogły mieć kontakt z substancją stwarzającą zagrożenie dla zdrowia lub życia. Publikacje naukowe wskazują, że możliwe jest także zanieczyszczenie lekami cytostatycznymi zewnętrznej powierzchni fiolek produkowanych przemysłowo leków lub zewnętrznych opakowań blistrowych po tabletkach [49][50][51][52].…”
Section: Odpady Po Lekach Cytotoksycznych I Cytostatycznych − Zasady unclassified